Association between serum albumin concentration change trajectory and risk of hypertension: a cohort study in China - Liu, Yinxing; Xu, Shan; Chen, Hongen; Dai, Shuhong; Hao, Jiejing; Chen, Xi; Zhang, Ji; Li, Siguo; Liu, Jun; Hu, Fulan; Lou, Yanmei; Wang, Changyi (Frontiers in Cardiovascular Medicine, 2024)
Background We sought to assess the risk of hypertension based on the trajectory of changes in serum albumin concentrations. Methods A total of 11,946 nonhypertension adults aged 30–60 years who underwent at least 3 medical examinations between 2009 and 2016 were included in this study. Group-based trajectory models were obtained for 4 category groups, and logistic regression models were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for each category group of serum albumin concentration and the risk of hypertension. Results During a mean follow-up period of 4.30 years, 1,537 hypertension events occurred in 11,946 subjects without hypertension. A high stable trajectory of serum albumin concentrations (OR, 0.70, 95% CI, 0.51–0.96) was associated with a significantly lower risk of developing hypertension. The results of the sensitivity analysis of the high stable trajectory (OR, 0.64, 95% CI, 0.43–0.96) remained statistically significant. Subjects with normal weight and those ≥45 years of age had a significantly lower risk of hypertension at moderate increase (P = 0.053 or 0.026) and high stable trajectories (P = 0.011 or 0.016). In males and overweight subjects, the risk of hypertension was significantly lower in the high stable trajectory (P = 0.038 or 0.044). Conclusion In this study, we found that moderate increase in serum albumin concentrations and a high stable trajectory were significantly associated with a reduced risk of hypertension in subjects aged ≥45 years and those with normal weight and that high stable serum albumin concentrations were significantly associated with a reduced risk of hypertension in males and overweight subjects.